Investigation of probiotic properties of Lactiplantibacillus plantarum isolated from hawthorn vinegar - Irmak Icen Taskin (CyTA - Journal of Food, 2024)
Probiotic microorganisms are gaining attention because of their beneficial effects on human health. Vinegar is produced by fermenting carbohydrate-rich foods with yeasts and acetic acid bacteria. Hawthorn vinegar is notable for its high concentration of aromatic compounds, amino acids, vitamins, minerals, and organic acids. In this study, probiotic bacteria was isolated from traditionally fermented hawthorn vinegar. Following genotypic characterization, the isolated bacteria was evaluated for its capacity to grow and survive in a low pH environment, antibiotic susceptibility, surface adhesion qualities, cholesterol precursor degradation, and adherence to HCT116 cells. The data indicate that the isolated strain is Lactiplantibacillus plantarum (L. plantarum IIT), and it exhibits probiotic potential. The strain can break down four distinct cholesterol precursors and was resistant to N30, K30, VA30 and S10 antibiotics. Additionally, it demonstrates a high adhesion capacity to HCT116 cells (96.63%) and exhibits cytotoxic effects on these cells.